Analysis of Purple Eggplant Growth After Vermicompost and NPK Fertilizer Treatment - I Wayan Merta; Ahmad Raksun (Postgraduate, University of Mataram, 2023)
Eggplant growth rate is determined by genetic and environmental factors. Environmental factors that affect eggplant growth include the availability of nutrients on agricultural land. Research on analysis of purple eggplant growth after vermicompost and NPK fertilizer treatment was carried out from March to July 2023. This study aims to analyze the effect of the application of vermicompost on the growth of purple eggplant. The application of NPK fertilizer on the growth of purple eggplant. The interaction effect of vermicompost and NPK fertilizer treatment on purple eggplant growth. Growth parameter data were analyzed using the F test. The results showed that: Vermicompost application increased stem height, total leaves and leaf length but did not increase leaf width and stem diameter of purple eggplant. The application of NPK fertilizer was effective in increasing stem height, total leaves, leaf length, leaf width and stem diameter of purple eggplant. The interaction of vermicompost treatment and NPK fertilizer was not effective in increasing all measured growth parameters.